Seashore paspalum in the Mediterranean transition zone: phenotypic traits of twelve accessions during and after establishment - Gaetani, Monica; Volterrani, Marco; Magni, Simone; Caturegli, Lisa; Minelli, Alberto; Leto, Claudio; La Bella, Salvatore; Tuttolomondo, Teresa; Virga, Giuseppe; Grossi, Nicola (Italian Journal of Agronomy, 2017)
The use of warm-season turfgrasses is consolidated in the transitional areas of Mediterranean countries and some field trials have provided information on the adaptability of seashore paspalum to Mediterranean environment. Nonetheless, little is known on the performance of the different commercial cultivars of Paspalum vaginatum in this climatic zone. Furthermore, considering the high degree of variability of this species, ecotypes have the potential to supply new plant material with desired turf characteristics. The research aimed at comparing growth characteristics and morphological traits of eight commercial cultivars of seashore paspalum (Platinum, Salam, SeaDwarf, Sea Isle 1, Sea Isle 2000, Velvetene, Marina and Sea Spray) and four ecotypes (CeRTES 101, CeRTES 102, CeRTES 103, CeRTES 104), during establishment and on mature turf grown in two Italian locations (Pisa and Palermo). Probably due to higher mean minimum temperatures a clear effect of location was recorded during the establishment year with fastest stolon growth rate and higher ground cover at 133 days after planting being registered in Palermo. Internode length and diameter, node density, horizontal stem density, turf quality and colour gave instead higher values in Pisa. On mature turf best colour ratings were of SeaDwarf and the ecotype CeRTES 104. The finest leaves were found in Sea Isle 2000 (1.5 mm) while the denser cultivars, and potentially the most wear resistant were Sea Isle 1, CeRTES 104, and Platinum. Top quality was scored for Sea Isle 1, Sea Isle 2000 and Platinum. Best performances for fall colour retention and spring green up were frequently associated with commercial cultivars. The relative ranking of the commercial cultivars for aesthetic and functional performance can be a tool for the decisions of turf managers while data of ecotype CeRTES 104 as to colour, shoot density and quality stimulate further research for the identifications of ecotypes with superior traits of visual quality and wear resistance.